Reduction of Salmonella and Ammonia Emissions in Broiler Litter Using Sulfuric Acid and Aluminum Sulfate - Williams, Z.T.; Macklin , K.S. (International Journal of Poultry Science, 2013)
In recent years an emphasis has been placed on reducing food borne pathogens on the farm. Of particular interest to the poultry industry is Salmonella enterica. In the United States, a common practice in broiler management is the reuse of litter for consecutive flocks; this practice can lead to a Salmonella positive flock causing the colonization of sequential flocks. Reuse of litter can also lead to high levels of ammonia volatilization which can impact broiler health and performance. In this paper, two experiments are presented using chemical litter amendments to reduce both ammonia and Salmonella. In the first experiment, liquid sulfuric acid was applied to litter at one of three application rates; 9.07, 18.14 and 27.21 L/92.9 m2. In experiment two, commercially available aluminum sulfate was applied to litter at three different application rates; 22.7, 45.5 and 68.0 kg/92.9 m2. In addition, a cocktail of five poultry associated S. enterica serovars was applied to the litter. Salmonella, ammonia, moisture and pH levels were measured immediately before treatments and every 24 hours up to 96 hours. For treated litter, a reduction was seen in ammonia levels 24 hours after application regardless of application rate, the reduction continued for the duration of the experiment (P